2010
DOI: 10.1007/s11055-010-9270-z
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Changes in the Functional Activity of the Neuroendocrine System: The Modulatory Activity of Derinat

Abstract: Changes in the functional activity of the hypothalamo-hypophyseal-adrenocortical system (HHACS) and hypothalamo-hypophyseal-gonadal system (HHGS) in conditions of different levels of stress and the possibility of correcting them using the native DNA formulation Derinat, which has immunomodulatory properties, were studied. The vectors of changes in hormonal reactions in both systems were found to be independent of the intensity of stress: there were increases in corticosterone levels and decreases in testostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…It can be assumed that this effect is associated with the influence of the combined effect of TLR9 + TLR4 agonists on the migration and proliferation of AP cells (Root-Bernstein 2021). Fomicheva et al it was shown that the preventive administration of Derinat ® at a dose of 10 mg/kg stimulates an increase in the level of testosterone and corticosterone in animals, against the background of cold stress, immobilization and the introduction of LPS, led to an increase and subsequent maintenance of a high level of these hormones for 24 h after the stressful impacts (Fomicheva et al, 2010). Maintaining high levels of testosterone and corticosterone is an effective mechanism for increasing the body's resistance to stress (Sapolsky et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that this effect is associated with the influence of the combined effect of TLR9 + TLR4 agonists on the migration and proliferation of AP cells (Root-Bernstein 2021). Fomicheva et al it was shown that the preventive administration of Derinat ® at a dose of 10 mg/kg stimulates an increase in the level of testosterone and corticosterone in animals, against the background of cold stress, immobilization and the introduction of LPS, led to an increase and subsequent maintenance of a high level of these hormones for 24 h after the stressful impacts (Fomicheva et al, 2010). Maintaining high levels of testosterone and corticosterone is an effective mechanism for increasing the body's resistance to stress (Sapolsky et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Since an increase in GDNF, NGF, or brain-derived neurotrophic factor (BDNF) has been reported for these treatments as well, the Лечение черепно-мозговой травмы Brain trauma treatment with Derinat 2021, Vol. 23,6 2021, Т. 23, № 6 administration of Derinat can also be an alternative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These Лечение черепно-мозговой травмы Brain trauma treatment with Derinat 2021, Vol. 23,6 2021, Т. 23, № 6 changes initiate dynamic and evolving processes that result in inflammatory, neurochemical and metabolic alterations [9,63,84].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DA is an important part in central nervous system; previous studies have demonstrated that DA's function disorder is associated with schizophrenia and Parkinson disease or some other mental abnormality [ 27 ]. In the chronic cold and humid stress condition, not only the pituitary-adrenal cortex system but also the sympathetic adrenomedullary system is involved; thus, contents of catecholamine are elevated in blood; besides, DA is precursor of NE [ 28 ]. In conclusion, long-term exposure to cold and humid stress is most likely to activate hypothalamic-pituitary-ovarian axis and sympathetic adrenomedullary system at a chronic excitatory state and increase the levels of monoamine neurotransmitters such as DA, NE, and EP which inhibit hypothalamus-pituitary-genital axis, while generating endocrine and immune function disorder [ 29 , 30 ], eventually exceeding body's autoregulation range, and it leads to ovarian failure.…”
Section: Discussionmentioning
confidence: 99%